Reirradiation with Cyberknife® fractionated stereotactic radiotherapy in adult recurrent low-grade gliomas (Annals of Medical Research, 2021)
Aim: We aimed to present our clinical experience in patients with recurrent LGG who underwent the fractionated stereotactic radiotherapy (FSRT) with Cyberknife®. Material and Methods: Ten patients with recurrent low grade glioma who had previously irradiated were treated with FSRT as a salvage treatment. At the initial diagnosis, the histology of the tumor was grade II astrocytoma or oligodendroglioma. Four of 10 patients underwent surgery as the primary treatment for recurrence.Results: The median prescription dose was 24 Gy (range 21-25 Gy) with a median fractionation number of 4 (range, 3-5 fractions). No concurrent chemotherapy was administered except one with radiological tumor upgrading. The median interval between the first diagnosis and recurrence was 95 months (range, 45-191 months). From the time point of re-irradiation, median survival was 15 months (range, 1-30 months). CyberKnife® FSRT was well tolerated by all patients. No acute or late side effects were recorded. With a median follow-up of 17 months, 3 patients died. Seven patients were alive with local tumor control in 5 and tumor progression in 2 patients.Conclusion: Fractionated stereotactic radiotherapy is a safe and effective salvage treatment for recurrent LGG. FSRT in adult recurrent LGGs showed encouraging short term results in this small number of cases. Prospective studies are necessitated as further evaluation.
Keywords: Cyberknife; radiosurgery; recurrent low grade glioma; re-irradiation; salvage treatment